ANALISIS PUTUSAN HAKIM TERHADAP TINDAK PIDANA KORUPSI DANA DESA DI KABUPATEN SUBANG ( Studi Putusan Nomor : 95/Pid.Sus-TPK/2024/PN Bdg ) - Nabila Subur Rizkia; Syahrul Anwar; Suradi (PT. Saha Kreasi Indonesia, 2025)
The incidence of corruption offences shows a trend of increasing every year, both in terms of the amount of losses suffered by the state and the number of cases that arise. Corrupt practices have spread throughout all levels of society, including among village heads who are involved in the misappropriation of village funds. This study aims to understand the implementation of criminal law against corruption offences related to village funds in accordance with legal decisions, explore the legal considerations used by judges when deciding on village fund corruption cases in decision No. 95/Pid. Sus-TPK/2024/PN Bdg, and analyse the view of corruption punishment according to National Criminal Law. The method applied is a normative approach, with this research being descriptive in nature. The data used included major and minor premises, with data collection sourced from journal literature, bibliographic studies, and the internet, while the analysis was conducted deductively. The findings of the study indicate that the application of criminal law, both formally and materially, in the case of corruption of village funds in decision No. 95/Pid. Sus-TPK/2024/PN Bdg, was carried out appropriately. From a substantive criminal law perspective, the actions of the defendant Muhamad Jamal contained elements of an offence in accordance with the subsidiary indictment presented by the panel of judges, which stated that the defendant was proven to have committed a criminal act of corruption as stipulated in Article 3 of Law No. 20 of 2001, which amended Law No. 31 of 1999 concerning the eradication of criminal acts of corruption. In deciding the case, the panel of judges considered both legal and non-legal aspects. However, in the author's view, the judges should have explored the non-legal considerations in greater depth, particularly the factors that weighed heavily against the defendant.